When aspirational talk backfires: the role of moral judgements in employees' hypocrisy interpretation - Lauriano, Lucas Amaral (Journal of business ethics, 2022)
Corporate social responsibility (CSR) aspirations by companies have been identified as a motivating factor for active employee participation in CSR implementation. However, a failure to practise what one preaches can backfire and lead to attribution of hypocrisy. Drawing on a qualitative study of an award-winning sustainability pioneer in the cosmetics sector, we explore the role of moral judgement in how and when employees interpret word-deed misalignment in CSR implementation as hypocritical. First, our case reveals that high CSR aspirations by companies raise employees’ moral expectations. Second, we develop a framework that explains variations in employees’ hypocrisy interpretations based on consequentialist and deontological forms of moral judgement. Our research advances a contextual view of hypocrisy, not as an objective characteristic of an organisation, but as an outcome of interpretative processes of perceived motives and results in CSR implementation. Our framework thereby explains why even highly committed organisations may face accusations of hypocrisy.